Different senses of one's place: Exploring social adjustment to home-based care services among family caregivers from minority ethnic backgrounds who have relatives living with dementia. (February 2023) - Gulestø, Ragnhild; Lillekroken, Daniela; Halvorsrud, Liv; Bjørge, Heidi
Western dementia care policies emphasise that family caregivers from minority ethnic backgrounds must become more engaged in healthcare services. However, research exploring experiences of receiving services such as home-based care, and thus adjustment to the service, among family caregivers from minority ethnic backgrounds who have relatives with dementia is still scarce. Therefore, inspired by Pierre Bourdieu's theoretical concepts of field, habitus and capital, we explored how family caregivers from different minority ethnic backgrounds justified decisions about whether to receive home-based care and their social adjustment to the service. Using empirical data from semi-structured interviews with nine family caregivers from different minority ethnic backgrounds, we demonstrated that different mindsets and available social resources gave rise to various actions. Although some family caregivers were optimistic about receiving home-based care, our findings point to tensions between the ideals of care practices and the organisational structures surrounding home-based care as a service. Among those who had experiences with home-based care, we found that organisational limitations, particularly in terms of efficiency demands and time constraints, influenced their behaviours and thus their social adjustments to the service. For some, these limitations eventually resulted in cancellation of the service. However, not all had the same opportunities to make these decisions, indicating that, although family caregivers from minority ethnic backgrounds receive home-based care, this does not necessarily entail a deficiency-free service. Furthermore, we argue that public discourses on this subject can be challenged by encouraging one to look beyond ethnic and cultural labels towards other factors, such as organisational structures, that might largely influence the use of home-based care among these family caregivers.